Extension of the discrete universality theorem for zeta-functions of certain cusp forms - Laurinčikas, Antanas; Šiaučiunas, Darius; Vaiginytė, Adelė (Nonlinear Analysis: Modelling and Control, 2018)
In the paper, an universality theorem on the approximation of analytic functions by generalized discrete shifts of zeta functions of Hecke-eigen cusp forms is obtained. These shifts are defined by using the function having continuous derivative satisfying certain natural growth conditions and, on positive integers, uniformly distributed modulo 1.
Keywords: Hecke-eigen cusp form; uniform distribution modulo 1; universality; zeta-function of cusp form